Phenolic compounds from the flowers of Rosa hugonis Hemsl. and their neuroprotective effects. (April 2023) - Zhang, Xia; Chen, Bin; Xie, Yuan; Hu, Yeye; Niu, Zhiqiang; He, Ziliang; Wang, Lun; Zhang, Guolin; Wang, Mingkui; Hu, Weicheng; Li, Fu
Abstract: The fragrant flowers of Rosa hugonis Hemsl. Contain abundant valuable rose oil and carotenoids. However, phytochemical investigation of this resource rich in phenolics with neuroprotective activity in vitro has been rarely reported. Purification of the 70% ethanol extracts from the flowers of R. hugonis by various chromatographic methods resulted in the isolation and characterization of five undescribed acylated flavonoid glycosides (Hugonisflavonoid A-E) together with forty known phenolics. The chemical structures of the undescribed compounds were elucidated by extensive analysis of their spectroscopic data and chemical methods. All the isolates were found from R. hugonis for the first time and evaluated for their neuroprotective effects on 6-OHDA induced injury in PC12 cells. Seventeen compounds displayed remarkable protective effects at concentrations of 10 μM. Hugonisflavonoid E can reduce excessive reactive oxygen species and up-regulate mRNA expression levels of superoxide dismutase 1 and catalase. Additionally, hugonisflavonoid E activated the phosphorylated proteins such as PDK1, Akt and GSk-3β. These findings suggested that R. hugonis could be a potential source for neuroprotective agents. Graphical abstract: Image 1 Highlights: Five undescribed flavonoid glycosides were isolated from Rosa hugonis Hemsl.. The structures of the undescribed compounds were elucidated by spectroscopic data. Seventeen compounds protected PC12 cells from 6-OHDA-induced injury. Hugonisflavonoid E attenuated 6-OHDA-induced oxidative stress in PC12 cells.